Rhythmic patterns of Malaysian English (MalE) speakers - Pillai, Stefanie; Muthiah, Anussyia; Wan Ahmad, Wan Aslynn Salwani (Springer, 2019)
Previous research on Malaysian English (MalE) has indicated that there are differences in the way that different ethnic groups produce some segments in English possibly due to transfer from distinct first languages. However, thus far, no study has investigated the rhythmic patterns of different ethnic groups in Malaysia. The present study examines the rhythmic properties of speakers from three ethnic groups: Malay, Chinese and Indians. Since previous research has shown that speaking contexts can affect rhythm, this study also investigates the extent to which different speaking styles (read and spontaneous speech) affect rhythm in MalE. The data comprised audio recordings of 12 female speakers from three different ethnic groups in Malaysia: Malays, Chinese and Indians. The speakers who were between 40 to 45 years old were all fluent speakers of English based on their educational and professional backgrounds. The speakers were recorded in two speaking contexts. In the first, they read a passage, and in the second context, they talked about themselves and their families. Two metrics were used to examine rhythm in both these speaking contexts: a normalised Pairwise Variability Index (nPVI) and VarcoV (the standard deviation of vocalic intervals divided by their means). The results were compared across the three ethnic groups. Based on the two metrics, there were no significant differences between the three groups. There were also no significant differences between the two speaking contexts for all three groups. The findings suggest that there may be a common rhythmic pattern in MalE that cuts across ethnic groups.